DNA microarray analysis using a smartphone to detect the BRCA-1 gene. Issue 1 (10th October 2018) - Prasad, Alisha; Hasan, Syed Mohammad Abid; Grouchy, Steven; Gartia, Manas Ranjan
Abstract : DNA microarrays are used to examine changes in gene expression of a large number of genes simultaneously by fluorescent labeling of complementary DNAs (cDNAs). Abstract : DNA microarrays are used to examine changes in gene expression of a large number of genes simultaneously by fluorescent labeling of complementary DNAs (cDNAs). The major bottleneck in implementing microarray technology in resource-limited settings lies in the detection instrument used for generating images of spotted oligonucleotides post-hybridization. While various methods such as a lateral flow assay have been presented to accomplish point-of-care disease detection, there is no simple and effective instrument available to gather spot images maintaining the standard microarray procedures. Nanotechnology based sensors connected with a portable smartphone readout system have the potential to be implemented in microarray technology. Here, we describe a portable fluorescence microarray based imaging system connected to a smartphone for detecting breast cancer gene expression (BRCA-1) from exon 11. This is based on the interactive binding of probe DNA to Cy3-target DNA. A paper-based microfluidics approach was used to demonstrate the DNA hybridization assay. The imaging principles of the assembled device named "FluoroZen" are similar to those of a fluorescence microscope. It uses two light spectrum filters, one to excite the fluorescent dye and the other to capture the emission spectrum. The images were acquired by using CCD cameras from FluoroZen. The smartphone integrated paper microfluidics platform presented here could be translated into clinical settings to perform point-of-care testing.